Boar spermatozoa maintain DNA integrity after cryopreservation using different concentrations of glycerol - Peña Jr., Santiago T.; Gummow, Bruce; Parker, Anthony J.; Paris, Damien B. B. P. (2022)
Despite its potential benefits, the application of frozen-thawed boar spermatozoa in commercial pig production is still very limited. Cryopreservation could induce sperm DNA damage causing reduced fertility and early embryo loss. Glycerol is a popular cryoprotectant used to improve motility and plasma membrane integrity during sperm freezing but the optimal concentration needed to prevent DNA damage without causing cell toxicity is unknown. Thus, the aim of this study was to determine the cryoprotective effect of different concentrations of glycerol on DNA integrity and motility of frozen-thawed boar spermatozoa. Using the TUNEL assay and flow cytometry, there was no significant difference in the percentage of sperm DNA damage between fresh or frozen-thawed sperm at 3%, 6%, and 8% glycerol (1.9 ± 0.4 vs. 3.5 ± 0.8 vs. 2.8 ± 0.5 vs. 3.0 ± 0.8% respectively; P > 0.05). While total and progressively motile spermatozoa were higher in fresh samples, other CASA motion parameters such as straight-line velocity, average path velocity, straightness, and linearity were generally higher in 3% and 6% glycerol-frozen than fresh samples (P = 0.05). At the concentrations tested, glycerol appears to protect DNA integrity of boar spermatozoa during cryopreservation while slightly enhancing some sperm motility parameters.
Keywords: Cryopreservation of organs, tissues, etc; Boar spermatozoa; Boars